Theology of the Old Testament - Jacob, Edmond; Heathcote, Arthur W.; Allcock, Philip J. (London, UK Hodder and Stoughton, 1958)
Includes bibliographical references and indexes.
First published in French : Neuchatel, Swit.: Delachaux & Niestle S.A., 1955
Keywords: Bible. O.T. -- theology